Avaliação do pós-tratamento do lodo de esgoto, proveniente de digestor anaeróbio, com casca e semente de manga - Oliveira, Nara Munick Cerqueira Lopes (2013)
In an attempt to pathogen reduction in sewage sludge there are several post treatments alternatives, such as thermal drying, lime stabilization, composting and others. The present study aimed to evaluate an alternative process to reduce pathogens in sewage sludge by using mango processing waste, which contains antimicrobial properties against gram-positive and negative bacteria. The sewage sludge from UASB reactor was stabilized for 30 days in drying bed and submitted to the sanitization process with different concentrations of mango’s peel (5, 10, 15, 20 and 30% (w/w)) and kernel seed (5, 10, 15, 20 and 30% (w/w)), with sewage sludge as a positive control and alkalinized sludge as negative control. It was monitored total and fecal coliforms, Salmonella spp., Enterococcus spp. and Escherichia coli concentrations over 90 days (at 0, 3, 7, 10, 15, 20, 30, 45, 60 and 90 days), as well as determination of total and volatile solids, moisture, total organic carbon, nitrogen, pH, phosphorus and viable helminthes eggs. The results indicated that the concentrations of carbon, nitrogen and phosphorus of treatments showed little variation during the trial period. At day 90, the levels of total and fecal coliforms were <3 MPN/g TS in positive and negative controls as well as in most of treatments with mango’s residues. The use of mango’s kernel seed or peel resulted in a reduction of 99.9999% of enterococci, 99.999% of E. coli and 99% of salmonella numbers present at the beginning of this evaluation. Although there has been a reduction in the levels of pathogens, the biosolids obtained still has restrictions for agricultural use, according to current Brazilian legislation: CONAMA Resolution 375/06 and Normative Instruction N0 64/2008 of the Ministry of Agriculture.